Absorção de nutrientes pela macroalga Gracilaria Birdiae (Plastino & Oliveira, 2002) sob diferentes condições físicoquímicas - Monteiro, Lorena Soares (2011)
Among marine resources, seaweeds have emerged as the one which have the largest industrial use. Their abundance and diversity make them a great source of raw material for countless products for human and animal use. More over seaweeds have a widely environmental importance, regarding to the atmospheric O2, water nutrients removing, fossil fuels, and also on the harvest of animals that eat marine algae. Shrimp culture is directly dependent on a good water quality for satisfactory production, therefore maintain the quality of shrimp farms effluent means to perpetuate the activity. Seaweeds absorb nutrients from the water and use them for their growth, while contribute to the environmental improvement of aquatic ecosystems. Gracilaria species stand out for the ability to quickly absorb large amounts of dissolved nutrients, not only organic, but also inorganic nutrients. This study aimed to evaluate the nutrients removal from the effluent water from a shrimp farm by the seaweed G. birdiae, in order to provide information for a possible integrated shrimp (Litopenaeus vannamei) and seaweed (G. birdiae) culture. For this, we used 25 containers, randomly distributed, with five treatments and five replications of 5, 10, 15 and 20 g of seaweed in 3 L of the effluent water from shrimp farm plus a control without seaweed. These procedures were performed with constant illumination and with a 12h light and dark photoperiod. The animals resistance of to periods of low oxygen, and the nutrients input generated by cultured animals have been checked. Each experiment lasted two weeks and the results showed that the alga G. birdiae has the capacity to withdraw from the shrimp farm effluent a satisfactory amount of ammonia and phosphorus in a short period of time, and still maintain, under illumination, sufficient concentrations of oxygen in the water. LISTA DE